Getting to the edge: protein dynamical networks as a new frontier in plant–microbe interactions - Garbutt, Cassandra C.; Bangalore, Purushotham V.; Kannar, Pegah; Mukhtar, M. S. (Frontiers in Plant Science, 2014)
A systems perspective on diverse phenotypes, mechanisms of infection, and responses to environmental stresses can lead to considerable advances in agriculture and medicine. A significant promise of systems biology within plants is the development of disease-resistant crop varieties, which would maximize yield output for food, clothing, building materials and biofuel production. A systems or “-omics” perspective frames the next frontier in the search for enhanced knowledge of plant network biology. The functional understanding of network structure and dynamics s is vital to expanding our knowledge of how the intercellular communication processes are executed. . This review article will systematically discuss various levels of organization of systems biology beginning with the building blocks termed “–omes” and ending with complex transcriptional and protein-protein interaction networks. We will also highlight the prevailing computational modeling approaches of biological regulatory network dynamics. The latest developments in the “-omics” approach will be reviewed and discussed to underline and highlight novel technologies and research directions in plant network biology.